1994
DOI: 10.1002/pat.1994.220051205
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic flexible chain polymers based on silicon

Abstract: Poly(dialkylsiloxane)s and poly(dialkylsilane)s form a similar type of columnar mesophase. Although, the polysilanes are stiffer than polysiloxanes, both classes of polymers may be considered to be flexible due to the ability to form chain‐folded crystals. Chain flexibility rather than the presence of chain stiffness determines whether the columnar mesophase is formed. A certain amphiphilic character does not appear to be required, as polysiloxanes with short side groups, e.g. polydiethylsiloxane display the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…1,2 The thermal stability interval of the mesomorphic state in PDPS is about 100 °C broader than that in poly(di-n-ethylsiloxane), PDES, which confirms the very strong dependence of the isotropization temperature on the side-chain length already documented for the first members of the family. 3,4 PDPS exhibits two crystalline modifications [3][4][5][6][7][8][9][10] and a mesophase for which a hexagonal columnar packing of the chains was suggested. 2,9 The hightemperature crystalline modification of PDPS was first described by Petersen et al 11 as tetragonal with a ) b ) 9.52Å and c ) 9.4Å, while the low-temperature modification was assumed to be monoclinic, but no lattice parameters were reported.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The thermal stability interval of the mesomorphic state in PDPS is about 100 °C broader than that in poly(di-n-ethylsiloxane), PDES, which confirms the very strong dependence of the isotropization temperature on the side-chain length already documented for the first members of the family. 3,4 PDPS exhibits two crystalline modifications [3][4][5][6][7][8][9][10] and a mesophase for which a hexagonal columnar packing of the chains was suggested. 2,9 The hightemperature crystalline modification of PDPS was first described by Petersen et al 11 as tetragonal with a ) b ) 9.52Å and c ) 9.4Å, while the low-temperature modification was assumed to be monoclinic, but no lattice parameters were reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the present paper, we report the first studies of crystal thickening in poly(di-n-propylsiloxane), PDPS, where there is a large range of accessible crystal thicknesses, as both folded and extended-chain crystals can form under ambient conditions. 8,9 PDPS exhibits two crystalline modifications, denoted R and β, [10][11][12][13][14][15][16][17] and a mesophase for which hexagonal columnar packing of the chains was suggested. 16,18 Recently, the structures of the R polymorph and the mesophase were revised.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 PDPS exhibits two crystalline modifications, denoted R and β, [10][11][12][13][14][15][16][17] and a mesophase for which hexagonal columnar packing of the chains was suggested. 16,18 Recently, the structures of the R polymorph and the mesophase were revised. 9 It was found that the unit cell of the R phase is pseudotetragonal and is characterized by the monoclinic space group C2/c (No.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Similar mesomorphic behavior is observed for a number of inorganic/organic hybrid polymers, such as polysiloxanes and polyphosphazenes. 13,14 We are currently investigating polycarbosilanes with n-alkyl side chains with respect to the formation of conformationally disordered phases. 15 The structural prerequisites for the formation of conformationally disordered mesophases for polysilylenes are still a subject of controversial discussions.…”
mentioning
confidence: 99%
“…Poly(di-n-hexylsilylene) (PDHS) has been investigated intensely with respect to conformational disordering and related electrooptical changes. 13 C as well as 29 Si magic angle spinning (MAS) NMR studies of Schilling 19 and Gobbi 20 have shown the onset of side chain and backbone mobility concurrent with the transition to the mesophase. We have prepared a C1-deuterated sample of poly(di-n-hexylsilylene) (PDHS), using the CD 2 group in the vicinity of the polymer backbone as a probe for local mobility.…”
mentioning
confidence: 99%